Concentrations of DDT metabolites in different food items and public health risk in Africa regions: systematic review and metal analysis - Dechasa Adare Mengistu; Abraham Geremew; Roba Argaw Tessema; Tara Wolfing (Frontiers in Public Health)
BackgroundDDT (Dichlorodiphenyltrichloroethane) is a synthetic organochlorine pesticide used in agriculture and mosquito control but later banned due to its harmful effects on humans. It persists in the environment, biomagnified through the food chain, and poses serious health risks, including reproductive defect, cancer, and nervous system disorders. DDT has a long half-life and potential of long-range transport and continuing to contaminate long after use and remains to pose a global environmental and health concern. Therefore, this review was designed to assess the concentration of DDT metabolites (p,p'-DDT, p,p'-DDD, and p,p'-DDE) in various food items and evaluate the health risk to consumers in the African.MethodsThe preferred reporting item for systematic reviews and meta-analysis (PRISMA) protocol was used to conduct this work. SCOPUS, PubMed, Web of Science, Google Scholar, DOAJ, national repository, and MedNar were used to retrieve articles from October 1, 2023, to January 20, 2024. Meta-analysis data visualized using a forest plot. A random-effects model was applied when heterogeneity existed in overall mean concentration of DDT metabolites. The subgroup analysis, meta-regression, and sensitivity analysis was conducted and the Joanna Briggs Institute Critical Assessment tool to assess the quality of the studies.ResultsThe overall mean concentrations of p,p'-DDT, p,p'-DDD and p,p'-DDE, regardless of the types of food items, were 0.188, 0.22, and 0.0878 mg/kg, respectively. Based on the type of food items, The current study found that residue levels of DDT metabolites in vegetables, milk, and cereals exceeded the Maximum Residue Limits (MRLs) set by FAO/WHO/EU (0.05, 0.02, and 0.05 mg/kg, respectively), while residue levels in meat, khat, and fruit were below the MRLs (5, 0.5, and 0.05 mg/kg, respectively). The findings of the health risk assessment revealed that consumers are prone to both carcinogenic and non-carcinogenic risks from DDT metabolites. The persistence and bioaccumulation of these metabolites, along with multiple exposure routes and improper handling, may increase long-term health risks, even at low doses. DDT metabolite levels in most food categories exceed recommended limits, posing significant health risks to consumers. To reduce reliance on DDT, effective and cost-efficient alternative insecticides and vector-control strategies must be developed. Promoting environmental management, improving housing, and implementing farm-to-fork risk-based actions, such as Hazard Analysis and Critical Control Points (HACCP), across the food chain are crucial to mitigating the adverse effects of DDT exposure in the African region.